Regionality of disease progression predicts prognosis in amyotrophic lateral sclerosis. Issue 7 (27th November 2015) - van der Kleij, Lisa A.; Jones, Ashley R.; Steen, I Nick; Young, Carolyn A.; Shaw, Pamela J.; Shaw, Christopher E.; Leigh, P. Nigel; Turner, Martin R.; Al-Chalabi, Ammar
Abstract : Amyotrophic lateral sclerosis (ALS) is a devastating neurological syndrome in which motor neurons degenerate relentlessly. Although the site of onset and the rate of spread have been studied extensively, little is known about whether focal as opposed to diffuse disease affects prognosis. We therefore tested the hypothesis that regionality of disease burden is a prognostic factor in ALS. We analysed clinical data from two large multicentre, longitudinal trials. Regionality was defined as the difference in progression rates in three domains as measured by the revised ALS Functional Rating Scale, omitting the respiratory domain from analysis. We used death by trial end as the outcome variable and tested this by logistic regression against predictor variables including regionality and overall rate of disease progression. There were 561 patients. Regionality of disease was independently associated with significantly higher chance of death by study end (odds ratio most diffuse against most focal category 0.354 (0.191, 0.657), p = 0.001), with a direct relationship between degree of regionality and odds of death. We have shown using clinical trial data that focal disease is associated with a worse prognosis in ALS. Measures of regionality warrant further independent consideration in the development of future prognostic models.